INDUKSI KALUS EMBRIOGENIK BEBERAPA GENOTIPE UBI KAYU (Manihot esculenta Crantz.) - Nugroho, Candra Catur (Jurnal Magrobis, 2017)
Somatic embryogenesis is one of the important steps in the in vitro propagation and crop improvement of cassava. The experiment was aimed to induce the formation of somatic embryos from immature leaves, shoot tips, and petioles explants on eight types of embryogenic callus induction medium. The research consisted of four experiments, each using UJ 5, Jame-jame, Gajah, and Adira 4 genotypes as explants. The results showed that immature leaves and shoot tips cultured on the MS + 20 g L-1 sucrose + 8 mg L-1 2.4-D medium and MS + 20 g L-1 sucrose + 10 mg L-1 NAA medium showed the highest numberand percentage ofexplantsformingcallus, fastest initiation of callus, highestcallusgrowth,and highest diameter of callus.Key word : Cassava, 2.4-D, NAA, somatic embryogenesis